Strategi pemasaran produk olahan ikan asin (studi kasus usaha ikan asin ibu Muriah di Desa Tapuhahi Kecamatan Rumbia Tengah Kabupaten Bombana Provinsi Sulawesi Tenggara) - Lukmana, Inra; Budiyanto; Rosmawati (Universitas Halu Oleo, 2022)
This research aims to determine the marketing strategy of salted fish products. This research uses a case study method and conducted at Tapuhahi Village, Central Rumbia District, Bombana Regency, Southeast Sulawesi during the period of February 2020. The types of data used were primary data and secondary data. Data were collected by using interview techniques, questionnaires, documentation, and literature studies. The data obtained were analyzed using a SWOT analysis. The results showed that the marketing strategy of IbuMuriah's salted fish products was: not using dangerous preservatives; expanding the marketing network by taking advantages of technological and information developments; registering the product brands at the Directorate General of Intellectual Property Rights (DGIPR) and the National Agency of Drug and Food Control (NADFC);use good of raw materials; use good of the drying area; improve the quality of salted fish which is vulnerable to competition; optimizing the production of salted fish because the rainy season hampers the process of salted fish production; choosing a strategic location; use good promotional activities in print and electronic media.